2006
DOI: 10.1111/j.1399-6576.2005.00888.x
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous tunnelling of an epidural catheter in a child with epidermolysis bullosa

Abstract: Sir,Epidermolysis bullosa (EB) is a rare inherited disorder characterized by excessive susceptibility of the skin and mucosae to separate from the underlying tissues after trivial mechanical trauma). Insufficient post-operative analgesia in a child with EB will result in an unsettled child who will pull at his/her dressing and be more prone to new bullae formation (1). Patient-controlled analgesia is difficult for a patient with EB because of limited finger function or syndactyly from skin lesions.We present t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Ultrasound guidance can be used for peripheral nerve blocks with generous use of gel to minimize skin abrasion when moving the probe. When a catheter is placed (epidural or peripheral nerve), it may be tunnelled subcutaneously if desired [ 53 ] then secured to the skin using silicone-based tapes and dressings (Mepitac®, Mepitel®, Mepilex®) or other soft non-adhesive dressings. Adhesive dressings and adhesive adjuncts should be avoided.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultrasound guidance can be used for peripheral nerve blocks with generous use of gel to minimize skin abrasion when moving the probe. When a catheter is placed (epidural or peripheral nerve), it may be tunnelled subcutaneously if desired [ 53 ] then secured to the skin using silicone-based tapes and dressings (Mepitac®, Mepitel®, Mepilex®) or other soft non-adhesive dressings. Adhesive dressings and adhesive adjuncts should be avoided.…”
Section: Resultsmentioning
confidence: 99%
“… Basic perioperative assessment and pain treatments should be used as for non-EB patients, with modification A All Goldschneider 2010 [ 41 ] (5a), Goldschneider 2010b [ 42 ] (5a) Transmucosal (including intranasal fentanyl and transbuccal opioids) should be considered for short procedures and pain of brief duration when intravenous and enteral routes are unavailable B All Manjushree et al ., 2002 [ 45 ] (2b); Borland et al ., 2007 [ 46 ] (2b); Desjardins et al ., 2000 [ 47 ] (2a) Perioperative opioid use must account for preoperative exposure, with appropriate dose increases to account for tolerance B All Hartrick 2008 [ 56 ] (1a), Mhuircheartaigh 2009 [ 55 ] (1a), Viscusi 2005 [ 54 ] (2a) Regional anesthesia is appropriate for pain resulting from a number of major surgeries. Dressing of catheters must be non-adhesive and monitored carefully C All Diwan 2001 [ 51 ] (5a), Doi 2006 [ 53 ] (5b), Englbrecht 2010 [ 52 ] (5a), Kelly 1988 [ 48 ] (5b), Sopchak 1993 [ 49 ] (5a), Yee 1989 [ 50 ] (5a) C. Skin wounds and related pain are the hallmark of EB of most subtypes. Prevention and rapid healing of wounds through activity pacing, optimal nutrition and infection control are important.…”
Section: Methodsmentioning
confidence: 99%
“…[ 23 ] Splenectomy and cholecystectomy performed under general anesthesia and continued epidural blockade have also been described. [ 24 ] In our study, peribulbar block was given in 56 (11.4%) cases using lignocaine, bupivacaine, and ropivacaine without any adverse events. Thus, all the anesthetic agents (local and general) used in our study were observed to be safe without encountering any adverse effects.…”
Section: Discussionmentioning
confidence: 92%
“…Alternatively, catheters may be tunneled under the skin. 31,52 In EB patients, catheters are commonly removed on the first postoperative day, but use of a peripheral catheter for as long as 5 days without complication has been reported. 21,53,54 Catheters should be removed as soon as feasible, balancing the benefits of analgesia with the risk of infection, which will vary depending on the location of catheter and proximity to chronic wounds.…”
Section: Anesthesia and Analgesiamentioning
confidence: 99%